2017
DOI: 10.3102/0013189x17703946
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Assumptions in Research Synthesis: A Critical Construct Synthesis Approach

Abstract: Research syntheses in education, particularly meta-analyses and best-evidence syntheses, identify evidence-based practices by combining findings across studies whose constructs are similar enough to warrant comparison. Yet constructs come preloaded with social, historical, political, and cultural assumptions that anticipate how research problems are framed and solutions formulated. The information research syntheses provide is therefore incomplete when the assumptions underlying constructs are not critically u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…For instance, Annells [32] pointed out that video dissemination may render research results ineligible for meta-synthesis. The usual practice in research syntheses is to "limit the literature search to only research published in peer-reviewed journals" (p. 135) [33]. Indeed, in preparing this paper, no meta-syntheses that included video disseminated research findings were found.…”
Section: Devaluation Of Video Researchmentioning
confidence: 99%
“…For instance, Annells [32] pointed out that video dissemination may render research results ineligible for meta-synthesis. The usual practice in research syntheses is to "limit the literature search to only research published in peer-reviewed journals" (p. 135) [33]. Indeed, in preparing this paper, no meta-syntheses that included video disseminated research findings were found.…”
Section: Devaluation Of Video Researchmentioning
confidence: 99%
“…The current project proposes a conceptual systematic review and mapping of the diverse strands and voices within the discourse of mindfulness in education. We see the essential tasks of this synthesis as integrating major aspects and themes found in the literature into a higher-order structure (Dixon-woods, 2005, Wolgemuth, Hicks & Agosto, 2017. Expanding the scope of previous reviews that focused on limited domains, our aim is to include all domains of implementation and conceptualization of mindfulness in education within one mapping of the field.…”
Section: Definition Of the Review Project: Need Aim And Orientationmentioning
confidence: 99%
“…In order to represent the diversity of curricular voices outlined above we began with a systematic literature search (Petticrew & Roberts, 2008, Wolgemuth et al, 2017. To find relevant articles, we conducted electronic searches using the following search engines: Sciencedirect, Google scholar and EBSCO host (which includes PubMed, PsychINFO, and ERIC).…”
Section: Search and Selection Processmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the recent concerns raised by Wolgemuth, Hicks, and Agosto (2017) regarding study inclusion and exclusion criteria in systematic review. Specifically, important information may be missed if studies are eliminated due to quality ratings when addressing research questions in limited fields of research or with vulnerable populations(Wolgemuth, Hicks & Agosto, 2017), such as this review. This perspective that the use of quality assessment should be determined by the research question is also supported by recent guidelines for scoping review byPeters et al (2015).An Excel document was used for recording coded data from the included articles and stored in a secure cloud-based storage to provide a clear audit trail and collaboration between article reviewers.…”
mentioning
confidence: 99%